Teachers' Perspectives on Technology-Based Media in ELT: A Case Study in Indonesian Islamic Junior High School - Morinda Marsilea Sidarta; Siti Asmiyah; Fitra Amaliya (FOSTER: Journal of English Language Teaching, 2025)
The use of technology-based media brings benefits for ELT; hence, teachers must understand and be proficient in using technology-based media. But apparently, there is potential that teachers may need to realise the benefits of using technology-based media in the classroom. This study explores teachers’ perspectives on the benefits of using technology-based media in English Language Teaching (ELT). To garner the data, the researchers used a qualitative approach using semi-structured interviews. The subjects were four English teachers in one of the Islamic schools in Surabaya. The findings indicate the teacher’s perspective that utilising technology-based media will yield numerous benefits, such as helping to design lesson planning, facilitating the organisation of teaching activities, raising student engagement and participation, simplifying the process of teaching material, and making it easier to assess and provide feedback to students. Therefore, this study significantly contributes to improving English teaching practices and expanding teachers’ understanding of technology-based learning media that are very beneficial when applied in English language learning.